Biomedical dimensions on human genome research - Maccioni, Ricardo B.; Muñoz, Juan P.; Maccioni, Cristóbal (Acta Bioethica, 2004)
The elucidation of the human genome constitutes a major paradigm. Besides its impact on our biological nowledge, the elucidation of the human genome will certainly exert a driving force on both medical research and practice in the future. As a paradigmatic discovery impacting medical research, the human genome has also increased public awareness concerning the risks and ethical problems associated with this advancement. Questions such as whether it is ethical to reveal to a patient that he may be suffering an incurable disease, that this information may negatively impact his quality of life are among the many concerns. From the beginning of the race to elucidate the human genome, it was agreed upon that it is necessary to assure the privacy of an individual genetic information. Therefore, it is critical to focus the discussion in a wide scope and integrative perspective, since myths appear that may produce distortions in the analysis. It is also important to trust that the scientific community, together with other public sectors of the society, will promote a debate associated with the positive and negative aspects of any new technology arising from the discoveries around human genome. It is not the scientific advances that cause bioethical problems, it is the decisions that society takes in terms of how this technology will be used.